Citraan dan Relasi Trikotomi Dalam Lirik Lagu Ryuusei no Kakeru 『流星のカケラ』Karya GReeeeN - Nur Hastuti; Anggita Prameswari (IZUMI, 2022)
Abstract Music is something that is universal and does not know the class of society, anyone can appreciate music even though he is not educated in the field of music. Music is used by many people as a medium to express themselves (can be in the form of ideas or values that they believe in), as well as entertainment because it contains lyrics that match the emotions that are being felt by someone, such as happy, sad, angry, nervous. , fear, jealousy, enthusiasm, ect. The objectives of this research are describing the imagery depicted in the lyrics and explaining the trichotomy relation contained in the lyrics of the song Ryuusei no Kakera by GReeeeN. Based on the results of research and discussion on the lyrics of the song Ryuusei no Kakera by GReeeeN are in the song Ryuusei no Kakera there are several types of imagery, namely 3 visual images, 1 tactile images, and 2 sensation images, consisting of feelings of love and peace.The trilogy relationships in this song are icons, indexes, and symbols. The icon in this song is monogatari or story. Then, there are two indexes found in this song. Meanwhile, the symbol used in this song is the ryuusei no kakera or meteor fragment.   Keywords: GreeeeN, imagery , icons, indexes,  song lyrics, symbols     gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor